INTERAKSI ANTARBUDAYA ETNIS BUGIS-MAKASSAR DENGAN ETNIS JAWA (STUDI MAHASISWA BUGIS-MAKASSAR DENGAN MAHASISWA ETNIS JAWA DI LINGKUNGAN KOS DI SEMARANG) - Riki Arswendi (Konvergensi, 2015)
Differences in cultural background has an influence on the emergence of anxiety and uncertainty that may cause potential conflicts or misunderstanding. So it becomes an interesting and unique way to study how individuals ethnic Bugis-Makassar with Javanese cope with anxiety and uncertainty they experience and how they resolve conflicts or misunderstandings. The purpose of this study was to determine how the experience of the interaction of individuals in intercultural interaction. The theory used in this research is a management theory Anxiety and Uncertainty (Gudykunts), the theory of self Disclosure De Vito and Supratiknya. This study used a qualitative approach which refers to the interpretive paradigm. The subjects in this study were students of ethnic Bugis-Makassar and Javanese living in the same boarding environment. Data analysis techniques used in this study refers to the method of Von Eckartsberg phenomenology. The experience of the data will then be grouped into three main themes, namely: 1) experience in conducting research informants intercultural interaction, 2) problems in the interaction, and 3) the role of interaction in the development of relations. Keywords: intercultural interaction, anxiety and uncertainty, culture shock